Trivselsmålinger i folkeskolen: Skal alle elever være lykkelige? - Wiedemann, Finn (Tidsskrift for Professionsstudier, 2024)
Since the school reform in 2014 all primary schools have been carrying out well-being-measurements. The article focuses on school leaders’ experiences with well-being measurements. Seven school leaders have been interviewed about their experiences. The theoretical assumptions are among other things evaluation theory. Readings and analyses of central literature about well-being in school and society are also used. The analyses points to a different practice in schools when it comes to the use of well-being measurements. At some schools they do have a symbolic and ritual function. At other schools they are used as a part of the schools social and pedagogical development. The introduction of well-being measurements can be interpreted as an attempt to take softer and more human related issues into considerations in the discussions of what schools and society we want. On the other hand, it can also be interpreted as an attempt to govern schools and institutions in new ways.